Chlamydia‐infected macrophages are resistant to azithromycin treatment and are associated with chronic oviduct inflammation and hydrosalpinx development. Issue 10 (11th September 2019) - Harvie, Marina CG; Carey, Alison J; Armitage, Charles W; O'Meara, Connor P; Peet, Jesse; Phillips, Zachary N; Timms, Peter; Beagley, Kenneth W
Abstract: Chlamydia infection remains the leading sexually‐transmitted bacterial infection worldwide, causing damaging sequelae such as tubal scarring, infertility and ectopic pregnancy. As infection is often asymptomatic, prevention via vaccination is the optimal strategy for disease control. Vaccination strategies aimed at preventing bacterial infection have shown some promise, although these strategies often fail to prevent damaging inflammatory pathology when Chlamydia is encountered. Using a murine model of Chlamydia muridarum genital infection, we employed two established independent models to compare immune responses underpinning pathologic development of genital Chlamydia infection. Model one uses antibiotic treatment during infection, with only early treatment preventing pathology. Model two uses a plasmid‐cured variant strain of C. muridarum that does not cause pathologic outcomes like the plasmid‐containing wild‐type counterpart. Using these infection models, contrasted by the development of pathology, we identified an unexpected role for macrophages. We observed that mice showing signs of pathology had greater numbers of activated macrophages present in the oviducts. This may have been due to early differences in macrophage activation and proinflammatory signaling leading to persistent or enhanced infection. These results provide valuable insight into the cellular mechanisms driving pathology in Chlamydia infection and contribute to the design and development of more effective vaccine strategies for protection against the deleterious sequelae of Chlamydia infection of the female reproductive tract. Abstract : This article examines how antibiotic treatment alters the pathological outcome of chlamydial genital infections. It also shows that antibiotic treatment alters macrophage activation and proinflammatory signaling, both of which contribute to chronic infection.